2000
DOI: 10.1016/s1010-7940(99)00357-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new device for quick sutureless coronary artery anastomosis in surviving sheep

Abstract: Quick coronary artery anastomoses without suturing on beating hearts can be completed with the new GraftConnector. The GraftConnector creates reproducible anastomoses in much less time than suturing, the per-operative mortality in the GraftConnector Group was accordingly lower. Long-time follow-up of the patency in surviving animals is pending. The presented device may ultimately permit quick anastomoses endoscopically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Our rationale for using sheep in this study is the fact that they share a number of developmental features with humans; and unlike rodents they typically produce singleton offspring. In addition, the sheep ITA been extensively utilised as a model for studying graft function following coronary artery bypass surgery [23,24]. In view of this, we believe it is reasonable to consider extrapolating the findings of our study to humans.…”
Section: Discussionmentioning
confidence: 79%
“…Our rationale for using sheep in this study is the fact that they share a number of developmental features with humans; and unlike rodents they typically produce singleton offspring. In addition, the sheep ITA been extensively utilised as a model for studying graft function following coronary artery bypass surgery [23,24]. In view of this, we believe it is reasonable to consider extrapolating the findings of our study to humans.…”
Section: Discussionmentioning
confidence: 79%
“…Numerous sutureless techniques have been developed for microsurgical anastomoses (stapling, laser welding, surgical glues). These methods have demonstrated some success but all are associated with difficulties or complications, [10][11][12][13][14][15][16][17][18][19] which impede them to largely diffusion in clinical practice. So, the gold standard in microsurgery still remains sutures with their adverse effects on vessels: vascular tissue trauma, foreign bodies reaction and risk of leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Sutureless techniques such as stapling, laser welding and surgical glues have been developed, tested and used in several animal and clinical studies to overcome or reduce suture‐related problems during vascular anastomoses1, 3, 14–20. Although these studies have demonstrated various successes, none of these techniques is without adverse effects, difficulties or complications1, 3, 14–20.…”
Section: Discussionmentioning
confidence: 99%
“…Sutureless techniques such as stapling, laser welding and surgical glues have been developed, tested and used in several animal and clinical studies to overcome or reduce suture‐related problems during vascular anastomoses1, 3, 14–20. Although these studies have demonstrated various successes, none of these techniques is without adverse effects, difficulties or complications1, 3, 14–20. Penetrating stapling causes vessel trauma, but non‐penetrating clips are ineffective as they do not enter the intima14, laser welding demands specific surgical skills and may result in thermal damage to surrounding tissue14, 17, and application of surgical glues can be associated with the risk of leakage into the vessel lumen and inflammatory reactions1, 3, 14.…”
Section: Discussionmentioning
confidence: 99%